If you can t face them, replace them - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Weeds just will not lie down and take 'No!' for an answer. After the umpteenth round of weeding, they shoot up again, ruining harvests and elbowing out crops altogether. If we understood better why weeds appear and re-appear we could work on better...